Association of Picky Eating with Growth, Nutritional Status, Development, Physical Activity, and Health in Preschool Children - Chao, Hsun-Chin (Frontiers in Pediatrics, 2018)
Background: This study aimed to assess the prevalence of picky eating among preschool children, and to evaluate the association between eating behavior and growth, physical activity, development, and health status. Methods: A structured questionnaire was used to conduct a cross-sectional descriptive study of 300 primary caregivers of children aged 2-4 years in Taiwan. Data collected included: demographics, food preferences, eating behavior, body weight and height, development, physical activity, and records of medical illness. Data from children defined as picky or non-picky eaters based on parental’ questionnaire responses, were analyzed and compared using standard statistical tests. Results: The mean age of the children was 2.95 years; 162 (54%) were picky eaters. Compared with non-picky eaters, z-score of weight-for-age, height-for-age, and BMI-for-age in picky eaters was 0.91, 0.73, and 0.44 SD lower, respectively. There were significant differences of rates in the weight-for-age, height-for-age, and BMI-for-age percentiles <15, between picky and non-picky eaters (P = 0.04, 0.023, and 0.005, respectively). Fear of unfamiliar places, poor physical activity, constipation and high frequency (>2 times in the past 3 months) of medical illness were significantly higher in picky eaters (P = 0.01, 0.001, 0.044, and < 0.001, respectively). Conclusion: The prevalence of picky eaters in preschool children was high, resulting in significant detrimental impacts on growth, nutritional status, development, physical activity, and health status.